Illegal immigrant entry into Sabah / Haijon Gunggut, Habibun Nisa Mohamed Ajmal and Zuraidah Zaaba - Gunggut, Haijon; Mohamed Ajmal, Habibun Nisa; Zaaba, Zuraidah (2006)
The study was conducted to compare policy statement and actual government stand on immigrants, especially illegal immigrants in Sabah. The time frame of this study began from the period of the USNO government to the present government. Historical study was employed using mostly newspapers reports and government documents. Statements by policy makers and the actual actions were analyzed to determine the actual government stand. Government policies before the eighties were far more accommodative, towards immigrants compared to later periods. The accommodating policy was partly due to the perception that the presence of immigrants was not threatening and, in fact, beneficial to the state. As more immigrants entered the country illegally, government policy towards the immigrants eventually became stricter and less accommodating. That is, the USNO and BERJAYA policies were more accommodating while the PBS and BN policies were less accommodating. This means that there was a gradual shift from "open door policy" towards zero tolerance of illegal immigrants. Immigration issues had become a serious concern since the early eighties. An important part of the problem was the need for foreign labor, which allowed an influx of immigrant workers to pour into the state. More importantly. Sabah was continuing to prosper as compared to Philippines and Indonesia. As long as this condition continues, there is always an attraction to migrate to Sabah. This tendency is aided by the long historical and cultural ties shared between the communities of Sabah, Philippines and Indonesia. Inconsistencies on the part of the policy makers towards immigrant population resulted in a lack of clear policy on how to deal with them, which the immigrants may have interpreted as an opportunity to stay in the state. Thus, although illegal immigrants are considered a threat, certain groups of immigrants such as foreign workers and refugees were fully accepted and even sought. Yet, the status of immigrant is not static. Legal immigrants like legitimate foreign workers may become illegal immigrants if their work passes are not renewed. This partly contributed to the difficulty in addressing the problem of illegal immigrant in the state.